Synthesis and Characterization of Novel Mn(II), Co(III), Ni(II) and Cd(II) Complexes from 4-(2-nitrophenylazo)-1H-pyrazole-3,5-diamine - Esener, Hasan; Adiguzel, Ragip; Ergin, Zuhal; Aktan, Ebru; Turan, Nevin; Sekerci, Memet (Amer Scientific Publishers, 2011)
In this study, the diazotized o-nitroaniline was coupled with malononitrile. The ring closure reaction of the obtained product with hydrazine monohydrate yielded 4-(2-nitrophenylazo)-1H-pyrazole-3,5-diamine (L). The structure of L has been elucidated by spectroscopic analyses. Then, novel Mn(II), Co(II), Ni(II) and Cd(II) complexes of L have been synthesized, and the structures of these complexes determined by elemental analysis, spectrometric and TGA/DTA methods, molar conductance and magnetic susceptibility measurements. All complexes were monomeric. Except Mn(II) complex, other complexes were diamagnetic. From the elemental analyses and mass spectra data, the complexes were proposed to the formulas [MnL2(CH3O)H2O]center dot Cl center dot CH3OH, [CoL2(CH3O)(2)]center dot Cl center dot 2.5CH(3)OH, [NiL2(CH3OH)(2)]center dot 6.5CH(3)OH and [Cd2L2(Cl)(2)(CH3O)(2)]center dot CH3OH center dot 1.5H(2)O. For Mn(II) and Co(III) complexes octahedral and for the Ni(II) complex square planar geometry were proposed, but the Cd(II) complex includes five coordinated structure. The Mn(II), Co(II) and Ni(II) complexes were found to be mononuclear and electrolytes. On the other hand Cd(II) complex was found to be dinuclear and non-electrolyte.
Keywords: 4-(2-nitrophenylazo)-1H-pyrazole-3,5-diamine and Metal Complexes; Azodyes Complexes